GC-MS ANALYSIS OF BIOACTIVE COMPONENTS OF FICUS RELIGIOSA (LINN.) STEM - M.S. MANORENJITHA; A.K. NORITA; S. NORHISHAM; M.Z. ASMAWI (International Journal of Pharma and Bio Sciences, 2013)
Ficus religiosa is one of the medically important plants belonging to the family Moraceae. It has been used extensively by ayurvedic practitioner in India to treat various ailments such as dysentery, snakebite, skin diseases and constipation. The aim of the study is to verify the presence of major chemical compounds and elucidate the chemical constituents contained in the Ficus religiosa stem. The stem showed positive results for the presence of alkaloids, saponins, tannins, triterpenes and steroids. Identification of chemical composition was conducted using the GC-MS equipped with mass detector supplied with helium. Thirteen chemical constituents have been identified based on NIST & WILEY libraries for botanical compounds. The major chemical constituents are 1,2-Benzenediol (9.85%), Caffeine (4.20%) and Stigmasterol,22,23-dihydro (1.81%).